Unemployment research in the conditions of the labour market transformation - Romanika, Tetiana (Technology audit and production reserves, 2020)
The object of research is the labor market, which is undergoing significant transformations under the influence of technological and structural changes, global and demographic trends. In this context, special attention should be paid to such an important aspect as youth unemployment, to identify its features. The subject of analysis is the classification of the causes of unemployment and the development of unemployment, youth behavior patterns on the labor market, manifested in the spread of phenomena such as distance employment, the latest forms of employment, self-employment, social exclusion of youth and the like. The methodology of an interdisciplinary approach to the analysis of youth unemployment made it possible to identify and characterize not only its state and structure, but also to identify the characteristics of youth behavior patterns in the labor market. The conclusion regarding the growth and actualization of employment instability, the decrease in the value of labor among youth, the blurring of the boundaries between employment and unemployment, as a result of modern transformations of the labor market, actualizes the need to search for a new youth policy. Analyzing the factors producing the growth of youth unemployment and the spread of non-standard forms of employment, it should be noted the need for their constant consideration in the institutional environment of the modern economy. The main manifestations of socio-economic transformations of the labor market are substantiated. It is proved that the effective inclusion of young people in social production is in the plane of the formation of an innovative model of social and labor relations based on the reform and creation of regulatory institutions. Without the development and implementation of effective and interconnected institutional mechanisms for managing the youth labor market, it is impossible to systematically and comprehensively increase the level of youth employment. The paper proposes the creation of a system of institutions, the main activity of which will be aimed at stimulating youth employment, identifying hidden employment and youth unemployment, employment, retraining, work with gifted youth, social guarantees and the like. Thanks to this, it is possible to tightly control the state of youth unemployment, to respond quickly and to implement prompt and effective measures to overcome it